The Role of University Resource Support and Entrepreneurial Characteristics On Halal Startup Businesses - Hendratmi, Achsania; Sukmaningrum, Puji; Nafik Hadi Ryandono, Muhamad (Indonesian Journal of Business and Entrepreneurship, 2022)
This study aims to determine the effect of university resource support, self-efficacy, entrepreneurial motivation, and entrepreneurial competence on halal startup business performance in Indonesia. This quantitative research uses the causal method to analyze the relationship between research variables. The research data was collected in 2021 using questionnaires to 130 students who have been running their businesses for at least the last three months. Statistical analysis using SEM-PLS showed that three of the four research hypotheses were accepted. The study's results found that university resource support and self-efficacy significantly affect the performance of the halal startup business. Meanwhile, entrepreneurial motivation does not positively influence student halal startup business performance. This research is expected to provide a contribution that can be a solution, suggestion, and recommendation that can be used as a reference for university decision-makers in Indonesia. The results of this study are expected to add to the repertoire of scientific literature, especially studies on the management of new halal businesses. Keywords: business performance, entrepreneurial competence, self efficiency, startup, universities education, universities support